Mekanisme Produk Pembiayaan Mudharabah Terhadap Nasabah Yang Membutuhkan Modal Usaha di BMT UGT Nusantara Cabang Kepanjen - Uni Khasanah; Istiqomah Istiqomah; Moh. Aan Sulton (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
development of sharia economics in Indonesia, sharia financial institutions, especially Baitul Maal Wat Tamwil, have the main goal of being able to help and alleviate problems, especially the problem of limited capital based on Sharia principles. Because many entrepreneurs have limited business capital. Therefore, with this research, entrepreneurs who need it will have information about the financing mechanism with a Mudharabah agreement, for those who have limited business capital. BMT UGT Nusantara has several financing products, one of which is the mudharabah contract. Mudharabah financing is an agreement where the shohibul maal provides funds to the mudharib with the profits divided according to the profit sharing and nibah agreed at the beginning of the contract. The mudharabah financing mechanism at BMT UGT Nusantara Kepanjen requires members to fulfill the requirements, then the BMT will carry out analysis and observations to ensure the eligibility of the recipient of the financing, if it has been approved they will inform you of the disbursement of funds and carry out an agreement. When the contract is executed, BMT and the customer enter into an agreement on the division of the ratio and margin. This research uses qualitative methods, with field research and interviews with BMT staff as a means of obtaining information